Hubungan Menonton Tayangan Video Ngaji Filsafat Akun Youtube MJS Channel dengan Respons Kebijaksanaan Viewers - Achmad Abdul Arifin; Muhammad Nur Kholish Abdurrazaq (Alhadharah: Jurnal Ilmu Dakwah, 2022)
The purpose of this study is to quantify whether or not there is a significant relationship, as well as the nature of the relationship, between watching the Ngaji Filsafat Video Show on the MJS Channel Youtube Account and the Viewers’ Wisdom Response. This method of study employed a quantitative approach with survey techniques and a questionnaire instrument. The audience and fans of the Ngaji Filsafat video uploaded by the MJS Channel on YouTube comprised the population of this study. The Lemeshow formula was used to determine the number of samples, which resulted in 100 respondents. Simple random sampling was used in the sampling technique. According to the results of this study, there is a significant relationship between watching the Ngaji Filsafat Video Show on the MJS Channel Youtube Account and the Wisdom Response of the Viewers. The chi-square test between the two dimensions reveals a significant relationship at the 95% confidence level. Furthermore, through the Spearman-Rank test, it shows that the correlation of the total score of viewers' answers on the two variables measured using an ordinal scale turns out to be a value of 0.528 and shows significance at the 95% confidence level and the correlation level is strong and unidirectional. That is, the higher the size of watching the show for viewers, the higher the policy response of viewers